From Ideas to Development The Determinants of R&D and Patenting - Jaumotte, Florence (OECD Publishing, 2005)
This paper uses panel regressions to investigate the effects of innovation policies and framework factors on business R&D intensity and patenting for a sample of 20 OECD countries over the period 1982- 2001. Both sets of factors are found to matter; the main determinants of innovativeness appear to be the availability of scientists and engineers, research conducted in the public sector (including universities), business-academic links, the degree of product market competition, a high level of financial development and access to foreign inventions. The effect of direct public financial support for business R&D is generally positive but modest, though it may larger for cash-constrained firms. Intellectual property rights appear to increase patenting significantly, but have little impact on R&D spending. Finally, the paper takes a closer look at the labour market for researchers, estimating jointly equations for employment and wages. Although the supply of scientists and engineers is eventually responsive to wage differentials, both with other professions and across countries, the evidence suggests that it may difficult to raise significantly the real amount of domestic R&D in the short run because the supply of researchers is relatively inelastic
Keywords: Economics